PENGARUH MODEL PEMBELAJARAN BLENDED LEARNING BERBASIS COMMUNITY OF INQUIRY (CoI) PADA MATERI STRUKTUR ATOM TERHADAP HASIL BELAJAR SISWA - Kinanti, Retno Limar; Refelita, Fitri (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
AbstractThis research aimed at knowing whether there was or not an effect and increase of values of Community of Inquiry (CoI) based Blended Learning model toward student learning achievement. It was Quasi Experimental research—a research that used an Experimental group and a Control group determined the difference of two variables. The samples of this research were 2 groups—the tenth-grade students of Natural Science 4 (the Experimental group) that were 36 students taught by using Community of Inquiry based Blended Learning model and the students of Natural Science 5 (the Control group) that were 34 students taught by using Conventional learning. The techniques of collecting the data were written pretest and posttest. The collected data were analyzed by using Independent Sample t test and to see the effect of using the coefficient of determination. The final data processing results obtained tcount of 1.778 while the value of ttable at a significant level of 5% = 1.684 then H0 is rejected and Ha is accepted. Means there is an influence of blended learning model based on community of inquiry (CoI) with conventional learning models on student learning outcomes. To determine the magnitude of the effect of the treatment used the coefficient of determination formula and the results obtained by 0.04, so the coefficient of influence (Kp) obtained is equal to 4%.Keywords : Blended Learning, Community of Inquiry, Learning Achievement, Atomic Structure and Periodic System of the Elements